Multisystem inflammatory syndrome in neonates (MIS-N): an updated systematic review - Muthiah, Divya; Chan, Ming; Low, Yue Wey; Ramasamy, Sheena Nishanti; Amin, Zubair; Chan-Ng, Pauline Poh Lin; Low, Jeen Liang; Low, Jia Ming (Frontiers in Pediatrics, 2024)
Introduction: To summarize and update clinical features and outcomes of Multisystem Inflammatory Syndrome in Neonates (MIS-N). Methods: A systematic literature search of studies on MIS-N published in PubMed, MEDLINE, EMBASE, CNKI and WHO COVID-19 databases from 1 December 2019 to 30 June 2023 was conducted. Reference lists of selected articles, Google Scholar and preprint servers were searched for additional studies. Methodological quality of included studies was assessed.Results: Of 1,572 records screened after the initial search, 35 studies involving a total of 201 neonates with MIS-N were included. One study was retrieved from pre-print server. For those with available data, 78.7% (37/47) of mothers were infected in the third trimester. Of the 199 mothers (two with twin pregnancy), 92.0% (183/199) were from India. The median age of neonates at presentation was 2.0 (IQR 1.0 -9.5) days. Over two-thirds (71.6%; 144/201) presented with respiratory distress, while 55.7% (112/201) had cardiac involvement such as ventricular dysfunctions, involvement of coronary arteries, and atrioventricular blocks.Arrhythmias and thrombosis were reported in 7.5% (15/201) and 3.0% of (6/201) respectively. All neonates, except one, required critical care; 40.0% (64/160) required inotropic support and 56.1% (105/187) required respiratory support, of whom 56.2% (59/105) were specified to require intubation. Mortality rate was 5.0% (10/201).Discussion/Conclusion: MIS-N should be considered in ill neonates presenting with 2 or more organ system involvement especially among those neonates with cardiorespiratory dysfunctions, in the presence of proven or suspected maternal COVID-19 infection during pregnancy.